Du prototype au marché - Victor Potier (Revue d'anthropologie des connaissances)
This paper uses the case of the serious game Fabric Game to study the process of marketing pedagogical innovation. Public authorities organize classroom "experiments" in school districts, where the game is kept at a prototype stage. Based on a four-year ethnography alongside the game designers, our study identifies the activity during these experiments as "prototyping": a collective and experimental activity designed to test and improve Fabric Game. In doing so, prototyping consists in producing knowledge about the game, but also in evaluating it in order to be exchanged, according to the sometimes contradictory testers' interests. The deconstruction of actors' roles and actions shows how the prototype serves to market pedagogical innovation: by producing sociotechnical mediations between designers and users, public actors enroll them in the channels for the financing and distribution of pedagogical inventions.